Alien boy [videorecording (DVD)] : the life & death of James Chasse - Lindstrom, Brian; Lindstrom, Brian; Lastra, Mike; Mayther, Betty; Moe, Randy (Breaking Glass Pictures, 2014)
Examines the death of James Chasse, a man suffering from schizophrenia, at the hands of the Portland, Orgeon police.